2014
DOI: 10.1007/978-3-319-07743-7_75
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Laser-Excited Spin Transport in Au/Fe/MgO(001): Relevance of the Fe Layer Thickness

Abstract: Propagation dynamics of spin-dependent optical excitations is investigated by back-pump front-probe experiments in Au/Fe/MgO(001). We observe a decrease for all pump-probe signals detected at the Au surface, if the Fe thickness in increased. Relaxation processes within Fe limit the emission region of ballistic spins at the Fe/Au interface to ~1 nm.Recently, we have established magneto-optical femtosecond back-pump frontprobe experiments [1 ] in order to provide insight into spin-dependent (i) transport contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Also, it implies that the full thickness of the OOP layer contributes to the generated spin current. The latter notion contradicts the idea of a limited interface region (≈1 nm) contributing to the spin current generation, as was suggested by Alekhin et al for Fe/Au [13]. In the case of a superdiffusive spin current, the spin current is generated due to spin filtering of the hot electrons in the magnetic layer [5].…”
Section: B Spin Current Generationmentioning
confidence: 83%
See 1 more Smart Citation
“…Also, it implies that the full thickness of the OOP layer contributes to the generated spin current. The latter notion contradicts the idea of a limited interface region (≈1 nm) contributing to the spin current generation, as was suggested by Alekhin et al for Fe/Au [13]. In the case of a superdiffusive spin current, the spin current is generated due to spin filtering of the hot electrons in the magnetic layer [5].…”
Section: B Spin Current Generationmentioning
confidence: 83%
“…This was first demonstrated in a collinear magnetic bilayer, where angular momentum transfer through the spacer layer resulted in a faster and larger demagnetization of the two antiparallel FM layers [10]. Several more recent studies have confirmed these laser-pulse induced spin currents [11][12][13][14][15][16]. It has even been claimed that the optically excited spin current can enhance the magnetization in one of the FM layers of the magnetic bilayer [12].…”
Section: Introductionmentioning
confidence: 84%
“…Ballistic Fe spins injected into a Au layer travelling close to the Au Fermi velocity arrive at the Au back interface within hundreds of femtoseconds while a diffusive component was detected at times up to 1 ps, in qualitative agreement with wave diffusion calculations [Kaltenborn et al ., 2012]. Variation of Fe layer thickness shows that the active injection region is an ≈1 nm thick Fe layer at the Fe/Au interface [Melnikov et al ., 2011; Alekhin et al ., 2015; Melnikov et al ., 2015], implying that superdiffusive transport is of limited importance for ultrafast demagnetization of significantly thicker ferromagnetic films, an observation supported by recent demagnetization experiments in Ni films [Schellekens et al ., 2013]. [Ando et al ., 2011; Hoffmann, 2013] used the inverse spin Hall effect to detect superdiffusive spin currents in non-magnetic layers.…”
Section: Interfacial Effects In Ultrafast Magnetization Dynamicsmentioning
confidence: 99%
“…Some experiments suggest different ways as to how the superdiffusive spin current generation is distributed along the multilayer, especial along FM1. Alekhin et al [57] deduce that in a layer consisting of Fe/Au films just a very thin interfacial region (around 1 nm) contributes to the spin current generation. On the other hand, Lalieu et al [35] show that, at least in a small range of thicknesses, almost the whole out-of-plane magnetized layer, consisting of Co/Ni thin films, is used for SC generation.…”
Section: Generation Of the Spin Currentmentioning
confidence: 99%